2014
DOI: 10.1177/0954411914543963
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of prototype handheld scanning probes for optical coherence tomography

Abstract: Three simple and low-cost configurations of handheld scanning probes for optical coherence tomography have been developed. Their design and testing for dentistry applications are presented. The first two configurations were built exclusively from available off-the-shelf optomechanical components, which, to the best of our knowledge, are the first designs of this type. The third configuration includes these components in an optimized and ergonomic probe. All the designs are presented in detail to allow for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…Another advantage of opting for OCT instead of an SEM is the possibility of assembling small, compact OCT mobile units and handheld scanning probes [18][19][20][21][22]. Such units make on-site evaluations possible.…”
Section: Resultsmentioning
confidence: 99%
“…Another advantage of opting for OCT instead of an SEM is the possibility of assembling small, compact OCT mobile units and handheld scanning probes [18][19][20][21][22]. Such units make on-site evaluations possible.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, OCT has been initially developed for ophthalmology [1], and it is usually focused on biomedical applications, including in skin, dentistry, or endoscopy [24]. For non-medical applications, OCT has been used especially for in-depth investigations of non-metallic (i.e., non-reflective) samples, in Non-Destructive Testing (NDT) of plastics and composites [25,26], electronic materials [27,28], dental materials [21,29,30], glass [31,32], or even art works like paintings [33]-to determine their internal structure, matrices and reinforcement, superficial stress, layer thickness, defects occurring inside layers.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrates that OCT can replace the SEM in the analysis of metallic surfaces broken in both a ductile and a brittle manner. 3) Another advantage of the OCT method as compared to the SEM is that the former can generate the image of the entire sample surface through consecutive scanning operations using an OCT mobile unit and handheld scanning probes [15,16]. These scanning operations do not destroy the metallic parts, which is an essential issue in the case of aviation, maritime, road or rail accidents, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A steel sample subjected to ductile fracture is considered as an example in the present paper. The tests carried out have been demonstrated that the OCT method is capable to replace the gold standard in this field, i.e., the SEM method, that has much higher resolutions, but also higher cost, and it is labor and time consuming; it is also strictly lab-based, in comparison with OCT, which can work as mobile units equipped with handheld scanning probes with galvoscanners [15,16] or Micro-Electro-Mechanical Systems (MEMS) [18], in order to perform in situ, industrial or forensic investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation